Pandemic Covid-19, Body Immunity Response, and Herd Immunity - Rina Tri Handayani; Dewi Arradini; Aquartuti Tri Darmayanti; Aris Widiyanto; Joko Tri Atmojo (LPPM STIKES KENDAL, 2020)
The World Health Organization has stated that COVID-19 is a